METAFORA KONSEPTUAL KATA ANAK DALAM KORPUS BAHASA INDONESIA - Regina Kolin (Journal of Education Papua Baru, 2026)
Abstract: This article condenses a thesis-based study on the conceptual metaphors of the Indonesian word anak using a corpus-linguistic perspective. The data were obtained from the Leipzig Corpora Collection and analyzed through a descriptive qualitative design supported by semantic interpretation. The analysis applies conceptual metaphor theory to classify metaphorical uses into structural, ontological, and orientational metaphors. The findings show that ontological metaphors are the most dominant because anak is frequently conceptualized as an entity or identity marker, as in anak bangsa and anak buah. Structural metaphors occur when the child-domain organizes non-biological relations such as anak asuh, while orientational metaphors appear limitedly in bodily constructions. This article argues that anak functions as a productive cognitive and cultural schema in Indonesian, revealing how kinship vocabulary extends into wider social, educational, political, and institutional meanings. Keywords: anak; conceptual metaphor; corpus linguistics; cognitive semantics; Indonesian language   Abstrak: Penelitian ini meringkas kajian berbasis tesis tentang metafora konseptual kata anak dalam bahasa Indonesia dengan pendekatan linguistik korpus. Data bersumber dari Leipzig Corpora Collection dan dianalisis melalui desain deskriptif kualitatif yang didukung penafsiran semantik. Kerangka analisis menggunakan teori metafora konseptual untuk mengelompokkan temuan ke dalam metafora struktural, ontologis, dan orientasional. Hasil kajian menunjukkan bahwa metafora ontologis paling dominan karena kata anak sering dikonseptualisasikan sebagai entitas atau penanda identitas, misalnya anak bangsa dan anak buah. Metafora struktural tampak pada hubungan non-biologis seperti anak asuh, sedangkan metafora orientasional muncul terbatas pada konstruksi tubuh. Penelitian ini menegaskan bahwa anak merupakan skema kognitif dan budaya yang produktif dalam bahasa Indonesia, serta menunjukkan bagaimana kosakata kekerabatan meluas ke dalam makna sosial, pendidikan, politik, dan kelembagaan yang lebih luas. Kata kunci: anak; metafora konseptual; linguistik korpus; semantik kognitif; bahasa Indonesia.